Persepsi Masyarakat Terhadap Praktik Qordh Pada Masa Covid-19 Perspektif KHES - Nur Bayyina Harianja; Syafri Gunawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study discusses the lending and borrowing of money carried out by the people of Pangurabaan Village, Sipirok District, South Tapanuli Regency in terms of the Sharia Economic Law Compilation. This type of research is field research with a qualitative approach, the primary data source in this study is the community who practice lending to loan sharks in Pangurabaan Village. Secondary data sources are in the form of books, journals and documents related to this research. Data collection techniques through observation, interviews and documentation. The data analysis technique is a descriptive type of research. The results of the study showed that the factor that influenced the community to borrow money from loan sharks was education, the education of the people of Pangurabaan Village was still low. Second, the work of most people in Pangurabaan Village who carry out loan transactions with loan sharks are farmers/planters and also traders. Third, the lack of working capital. Fourth, the time needed to get money/business capital is faster and easier. Fifth, family economic factors that are not fulfilled. Not everyone can meet the financial value of his family.